(untitled) (Al-Academy, 2024)
Design is a creative field that requires creating unusual solutions. For that, many educational institutions focus on preparing a designer capable of creative thinking by unusual using teaching methods. This empirical analytical study focused on applying the Random Juxtaposition method to generate ideas and form creative solutions in the field of advertising design, to achieve the three principles of creative thinking: fluency, flexibility, and originality. To conduct this study, an experiment was applied to a sample graphic design students. The experiment focused on combining two random words (noun + adjective). Then, finding relationships between them using a mind map. The results are: The random juxtaposition method is an effective method for generating ideas that achieve the principles of creative thinking - Mind map is contributed to obtaining endless deep ideas - Using creative methods helps break the creative block - Diversity in teaching methods creates enthusiasm within the studio and gives students new skills. This study recommends conducting further research that focus on employing the random juxtaposition method in other fields of arts and design.